Numerical heat transfer from Al2O3/water nanofluid through square cross-sectional duct with single- and two-phase models - Ozgen, Filiz; Kamaci, Gurcan (Springer, 2022)
The high cost of producing nanofluids and setting a high-technology experimental setup have led the researchers to use numerical simulations to investigate the effects of nanofluids on heat transfer. In this study, a representative Computational Fluid Dynamics (CFD) analysis by means of ANSYS-Fluent was performed to show the effects of Al2O3/water nanofluid on average heat transfer coefficient, for the case of flowing fluid through a square cross-sectional duct with single- and two-phase models. For 0.5% Al2O3/water nanofluid, the average deviation rate of the single-phase homogeneous model was 3.35%, whereas Eulerian Mixture Model (EMM) yielded an average result that was 19.87% higher than the reference experimental results. Similarly, for 1.5% and 2.5% Al2O3/water nanofluid, the average deviation rate of the single-phase homogeneous model was found to be 5.25%, %3.35, whereas the EMM yielded an average result, which was 39.59%, 49.47% higher than the reference experimental results, respectively. The comparison of the numerical results from different phase models with the reference experimental data showed that Single Phase Homogenous Model (SPHM) produced closer results to than EMM. The reason behind the high deviation rate from the reference experimental results was found to be the thermal conductivity equation. The thermal conductivity equation in the two-phase EMM was replaced with the Maxwell thermal conductivity equation. By this replacement, for EMM-II model for 0.5%, %1,5 and %2.5 Al2O3/water nanofluid, the average deviation rate from the reference experimental data was found to be 17%, 2.61% and %3.8. The reinterpreted EMM was observed to be the model that gives the closest results to the reference experimental data.
Keywords: Single-phase homogeneous model; Eulerian-mixture model; Nanofluid; Numerical analysis; Average heat transfer coefficient